2008
DOI: 10.1086/591228
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid Modeling of AGN‐driven Turbulence in Galaxy Clusters

Abstract: Hot, underdense bubbles powered by active galactic nuclei (AGNs) are likely to play a key role in halting catastrophic cooling in the centers of cool-core galaxy clusters. We present three-dimensional simulations that capture the evolution of such bubbles, using an adaptive mesh hydrodynamic code, FLASH3, to which we have added a subgrid model of turbulence and mixing. While pure hydro simulations indicate that AGN bubbles are disrupted into resolution-dependent pockets of underdense gas, proper modeling of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 96 publications
(146 reference statements)
5
86
0
Order By: Relevance
“…Our MHD simulations confirm the findings of previous hydrodynamic simulations that AGN-driven turbulence is local and non-volume-filling (Scannapieco & Brüggen 2008;Heinz et al 2010;Gaspari et al 2011;Vazza et al 2013). It is also in agreement with a recent study by Reynolds et al (2015), which showed that the generation of volume-filling turbulence by AGNsrequires that the g-waves are not trapped only within a small area.…”
Section: Hbi With Agnsupporting
confidence: 92%
“…Our MHD simulations confirm the findings of previous hydrodynamic simulations that AGN-driven turbulence is local and non-volume-filling (Scannapieco & Brüggen 2008;Heinz et al 2010;Gaspari et al 2011;Vazza et al 2013). It is also in agreement with a recent study by Reynolds et al (2015), which showed that the generation of volume-filling turbulence by AGNsrequires that the g-waves are not trapped only within a small area.…”
Section: Hbi With Agnsupporting
confidence: 92%
“…This closure is based on ideas of Woodward et al (2006) and features a nonlinear term in addition to a linear eddy-viscosity term. In general, the turbulence energy cascade is an important source of SGS turbulence energy production in turbulent flows, and it should not be neglected even if other subresolution sources are emphasized in particular astrophysical applications (e.g., Scannapieco & Brüggen 2008;Joung et al 2009). Our proposed closure for the transfer of energy by the turbulent cascade complements theses models.…”
Section: Resultsmentioning
confidence: 99%
“…Churazov et al 2004;Gaspari et al 2011bGaspari et al , 2012b, the evolution of filaments and bubbles (e.g. Scannapieco & Brüggen 2008), or the reacceleration of cosmic rays (e.g. Brunetti & Lazarian 2007).…”
Section: Introductionmentioning
confidence: 99%